Structural health monitoring of PPVC connectors - Phua, Yi An (Nanyang Technological University, 2020)
Modular construction and precast elements has been increasingly popular around the world. Prefabricated and prefinished volumetric construction (PPVC) has been the one of the advanced research topics of precast structural members. Arguably, PPVC has been around for a decade but little research is done on the implementation of a structural health monitoring (SHM) system on PPVC. SHM systems will provide real-time data related to structural integrity. A SHM system will enable engineers to make better assumptions on current health of PPVC units and will help to complement laboratory test results and computer models. With this direct data provided by a SHM system, it will be easier to foresee structural failures and assess extent of damaged structures. This project will research on the possibility of a SHM system in PPVC units. Various PPVC connection details will be analyzed and compared to a proposed PPVC system. Current SHM systems will also be reviewed to increase the feasibility of implementing a system in the selected PPVC system. Following on, testing will be conducted on specimens that mimic the connection system. Finally, the results and recommendations to a SHM system in PPVC will be discussed with suggestions for further testing procedures. The study will consist of two reports CT21AB-1 and CT21AB-2 with this paper being CT21AB-1.